STUDY ON THE CORRELATION BETWEEN STIFFNESS AND HARDNESS OF RUBBER PARTS BASED ON MOONEY-RIVLIN MODEL (MT) - WANG YuanShao; NIE ZiHao (Jixie qiangdu)
To reduce the raw material waste problems and repeated trial production in the matching process of rubber parts hardness and stiffness, the correlation analysis of rubber parts stiffness and hardness was carried out. Based on a rectangular rubber spring cushion, with uniaxial compression and tensile tests, the theoretical parameters of the Mooney-Rivlin model were calculated, and the results were verified by the least square method. The stiffness of the rectangular rubber spring pad increases nonlinearly with the increase of deformation, which Abaqus calculated. Based on the experimental data of rubber hardness, the exponential quadratic nonlinear function of hardness and Mooney-Rivlin model parameters was established. As a result, the hardness of rubber was positively correlated with the material parameters. The relationship between elastic modulus and hardness was transformed into elastic modulus and material parameters C2 and C1. Furthermore, the stiffness displacement curve of rubber material was obtained by simulation analysis to find the relationship between rubber material parameters and stiffness. Finally, with Mooney-Rivlin model parameters as the bridge, the correlation conclusion between stiffness and hardness of rubber parts was obtained.